ANALISIS ALIRAN DAYA TIGA FASA DENGAN METODE KOMPENSASI ADAPTIF UNTUK SISTEM DISTRIBUSI DENGAN UNIT PEMBANGKIT YANG TIDAK TERPUSAT - Muljono, Agung Budi; Nrartha, I Made Ari (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2007)
Generally study of power-flow used the system presentation with the well-balan-ced load. Presentation like this enabled to solve power-flow used single phase presen-tation. Well-balanced load distribution system is very rare. Condition of unbalance load on distribution system needed the special power flow program which can solve three phase power system.This research made and tested three phase power-flow program with adaptive compensation-based method using the application program MATLAB 6.5.1. This method emphasized to solve power-flow of radial system with balance or unbalance load and dis-persed generation. Result of research showed for the validation of program using standard data 15 bus that is getting of converged to the specified tolerance value (1x10-8) for the various lo-ading condition. Unbalance load caused the power mismatch at same iteration tend to in-crease in linear. Addition load factor at one of phase (phase A) caused power mismatch at same iteration tend to increase by exponential. Dispersed generation gives decrease voltage drop in most of all buses and decrease power loss until 73,64 %. Unbalance load on Airlangga feeder caused increase system loss until 38,09%. The biggest contributions of loss cause by longest branch feeder on bus 4 to 6 equal to 39,68 %. Biggest voltages drop at the end of feeder with average degradation until 0Ã0,0130 pu for balance and un-balance load.